2020
DOI: 10.18400/tekderg.456752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modeling Beam-Column Joints on Performance Assessment of Columns in Non-Ductile RC Frames

Abstract: Seismic performance evaluation of non-seismically detailed reinforced concrete (RC) buildings requires proper analytical modeling approaches for beam-column joints which are most vulnerable parts. This study investigates the influence of beam column joint modeling assumptions on performance evaluation of non-ductile RC buildings. Numerical simulation model includes truss-based elements for beam-column connections and fiber-based elements for beams and columns. Two-dimensional four-and six-story reinforced conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…U4 kolon-kiriş birleşimi numunesinin donatı detayları (Pantelides v.d., 2002) Şekil 8. Kolon-kiriş birleşimi için oluşturulan hibrit sayısal model (Girgin, 2019) Kolon-kiriş birleşimine kiriş ucundan tek yönlü (monotonik) olarak yükleme etkitilen sayısal model ile elde edilen yük-yerdeğiştirme grafikleri Şekil 9'da verilmiştir. Deneysel çalışmada ulaşılan en büyük yük değeri ile kıyaslandığında sayısal model ile yük değerinin 1.1 katı olarak hesaplanmıştır.…”
Section: Kolon-kiriş Birleşimi Testinin Modellenmesiunclassified
“…U4 kolon-kiriş birleşimi numunesinin donatı detayları (Pantelides v.d., 2002) Şekil 8. Kolon-kiriş birleşimi için oluşturulan hibrit sayısal model (Girgin, 2019) Kolon-kiriş birleşimine kiriş ucundan tek yönlü (monotonik) olarak yükleme etkitilen sayısal model ile elde edilen yük-yerdeğiştirme grafikleri Şekil 9'da verilmiştir. Deneysel çalışmada ulaşılan en büyük yük değeri ile kıyaslandığında sayısal model ile yük değerinin 1.1 katı olarak hesaplanmıştır.…”
Section: Kolon-kiriş Birleşimi Testinin Modellenmesiunclassified
“…Consequently, brittle shear failure of the connection will be triggered immediately after the shear stresses introduced to the joint exceed its shear capacity [5,6]. It is worth emphasizing that damage evolution and the extensive degradation of the overall bearing capacity are extremely rapid when the joint is totally unconfined or poorly confined [7,8]. Nevertheless, the joint shear failure cannot be effectively prevented solely by adding ties and by ensuring that the capacity design ratio value is higher than 1.30 (according to Eurocode 8), unless the developed shear stresses are limited to one half of the joint shear capacity (or lower) [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the axial load is an effective factor in the parameters of joint behavior. Girgin [19] studied the effect of modeling assumptions for column-beam connections on the performance evaluation of nonductile reinforced concrete buildings. Numerical model was constructed with nonlinear truss elements for column-beam connections and fiber-based elements for beams and columns.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical model was constructed with nonlinear truss elements for column-beam connections and fiber-based elements for beams and columns. Two-dimensional four-and six-storey reinforced concrete frames were analyzed by performing incremental dynamic analyses [19]. Sahutoglu and Tasligedik [20] studied an N-M interaction model for joints accounting for axial load level changes and verified the model with an actual structure damaged in the Christchurch Earthquake (2011).…”
Section: Introductionmentioning
confidence: 99%